HARMONI VOKAL PADA PROSES FONOLOGIS KOSAKATA SERAPAN BAHASA ARAB KE DALAM BAHASA BIMA - Nurul Maulidan (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
Vowel harmony is a vocal change that is caused by the influence of other vocal sounds that correspond to certain characteristics. This change is included in the sound insertion process. The theory used is transformational generative phonology with distinctive features to distinguish the characteristics of sound that is changing. This research is a qualitative descriptive study because the research data are in the form of words or phrases, not numbers. The data used in this study are absorption words in the Bima language borrowed from Arabic obtained from the Bima-Indonesian Dictionary. The method used in providing data is the refer to method. Based on the analysis found vocal harmony in the four vocal sound insertion processes, namely sound insertion [a], sound insertion [i], sound insertion [u], and sound insertion [o].